TAFSSA District Agrifood Systems Assessment in Bangladesh 2023: Local Market and Retail Census - International Rice Research Institute; International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative aimed at advancing equitable access to sustainable healthy diets, enhancing farmers' livelihoods and resilience, and conserving natural resources such as land, air, and water across South Asia. The TAFSSA district agrifood systems assessment seeks to establish a robust, accessible, and integrated evidence base that connects farm production, market access, dietary patterns, climate risk responses, and natural resource management, with gender considerations integrated throughout. The assessment focuses on rural areas in Bangladesh, India, and Nepal, utilizing a district-level, multi-year approach. Data collection was conducted between December 2022 and January 2023 in the Rangpur and Rajshahi districts of Bangladesh. The study employed a census across 50 villages per district, selected based on the probability proportional to the number of households in each village. The census included all formal and informal multi-vendor markets offering diverse food products, as well as retail food shops within the selected villages. Multi-vendor markets considered in the census included village markets, weekly village markets, roadside/street markets, and wholesale markets (mandis). Retail food shops included local grocery stores, vegetable/fruit shops (green grocers), and specialized shops selling meat, eggs, fish, or dairy products. A pretested, structured questionnaire was used for the census. Data collected included details on vendor density, vendor characteristics, operating hours and days, types of products sold, infrastructure and facilities in shops, waste disposal methods, and GPS coordinates of retail shops and markets.